KEBIJAKAN DAN PERAN LINTAS SEKTOR PEMERINTAH DALAM PENANGGULANGAN MASALAH STUNTING PADA ANAK DI KOTA BEKASI - Rifa’at Hanifa Muslimah; Gunawan Widjaja (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Currently, nutritional problems in Indonesia are still in the spotlight, one of which is about stunting in toddlers. The government shows its commitment to tackling stunting by making regulations on the acceleration of stunting reduction as stipulated in Presidential Regulation Number 72 of 2021. Stunting prevention requires good cooperation between government and non-government sectors to implement integrated and sustainable interventions. This study aims to provide an overview of the Bekasi City government policies in stunting prevention in Bekasi City and can provide an overview of cross-sectoral participation in the Government in stunting prevention. The writing method used is normative juridical, with a statutory approach. The data used is secondary data obtained from the study of literature. The analysis was carried out qualitatively. The result of this research is that the Bekasi City Government has formed a policy on Stunting Prevention and Control as stated in the Bekasi Mayor's Instruction No: 440/1914/Bappeda and on the Establishment of the Task Force for the Acceleration of Stunting Prevention and Control as stated in Decree Number: 440/Kep.277-Bappelitbangda/V /2020. In the Decree Number: 440/Kep.277-Bappelitbangda/V/2020 concerning the Establishment of the Task Force for the Acceleration of Stunting Prevention and Control and in the Bekasi Mayor's Instruction No: 440/1914/Bappeda concerning the Prevention and Control of Stunting, it has included cross-sectoral participation in the Government to overcome stunting, but implementation in the inter-sectoral field of government has not run optimally. The author hopes that cross-sectoral government can work together and coordinate with each other so that inter-sectoral programs can be perfect to achieve the same goal.